A Bioinspired Photothermal Pneumatic Device Enabling Optical Manipulation of Microfluid toward Precise Control of Microreactions. Issue 12 (14th October 2019) - Lv, Xuande; Wang, Wenzhong; Yu, Haifeng
Abstract : Various driving methods are developed in microfluidic technology to manipulate small amounts of liquid. Among them, the photocontrol method is highlighted for its advantages in contactless and accuracy control. However, the illumination method may induce risks of radiation damage, thermal damage, or chemical environment changes. To avoid these risks, a photothermal pneumatic microfluidic device (PPMD) containing a photothermal composite, an air chamber, and a tube is designed, bioinspired by the feeding process of female mosquitos. One way to drive liquid columns at a constant velocity higher than 1.0 cm s −1 in microtubes without interface modification is successfully obtained, and a method to separate out water–oil two‐phase liquid mixtures is proposed. The integration of several single PPMDs enables complex logical operations (AND and OR) toward precise control of microreactions. This work is promising in fields of microfluidic chips, pneumatic devices, liquid transfer, microreactions, and water–oil phase separation. Abstract : A bioinspired photothermal pneumatic microfluidic device (PPMD), with a tube as thin as 0.1 mm in internal diameter, is demonstrated. The driving mechanism is the photothermally induced volume changes of air in a chamber. The results indicate that small amounts of liquid can be driven in a PPMD at a constant velocity higher than 1.0 cm s −1 .